![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = 4 [ ( sin 2 α + cos 2 α ) 2 - 2 sin 2 α cos 2 α ] - cos4α
= 4 ( 1 - sin 2 2 α / 2 ) - 1 + 2 sin 2 2 α = 3
![](https://rs.olm.vn/images/avt/0.png?1311)
A = cos 6 x + 3 sin 2 x . cos 2 x + 2 sin 4 α . cos 2 x + sin 4 α
= cos 6 x + 3.(1 - cos 2 x ) cos 4 x + 2 sin 4 α . cos 2 x + sin 4 α
= cos 6 x + 3 cos 4 x - 3 cos 6 x + 2. sin 4 α .(1 - sin 2 x ) + sin 4 α= cos 6 x + 3 cos 4 x - 3 cos 6 x + 2 sin 4 α - 2 sin 6 x + sin 4 α
= -2.( cos 6 x + sin 6 x ) + 3 cos 4 x + 3 sin 4 α
= -2.( cos 6 x + sin 6 x ) + 3.( cos 4 x + sin 4 α ) = 1
Vậy biểu thức A không phụ thuộc vào x.
![](https://rs.olm.vn/images/avt/0.png?1311)
A = 2 ( sin 2 α + cos 2 α ) ( sin 4 α + cos 4 α - sin 2 α cos 2 α )
- 3 ( sin 4 α + cos 4 α )
= - sin 4 α - cos 4 α - 2 sin 2 α cos 2 α
= - ( sin 2 α + cos 2 α ) 2 = - 1
![](https://rs.olm.vn/images/avt/0.png?1311)
Sửa đề: sin^4x+cos^4x+1
\(A=\dfrac{\left(sin^2x+cos^2x\right)^3-3sin^2xcos^2x+2}{\left(sin^2x+cos^2x\right)^2-2sin^2xcos^2x+1}\)
\(=\dfrac{3\left(1-sin^2xcos^2x\right)}{2\left(1-sin^2xcos^2x\right)}=\dfrac{3}{2}\)